Comparative Analysis of Optical Signals Emitted by Corona on a Laboratory Model of Transmission Lines Made of Various Materials - Sławomir Krzewiński; Paweł Frącz; Ireneusz Urbaniec; Tomasz Turba (Journal of Spectroscopy)
The paper presents results of comparative analyses of optical signals generated by corona discharges occurring in the vicinity and on the surface of power transmission lines made of five different materials under laboratory conditions. Three aluminium-based materials were chosen: pure aluminium, aluminium with added magnesium, and aluminium with added silicon, and for comparison purposes also, steel-based lines were considered: copper-coated steel and steel with added chromium and nickel. A three-phase triangular arrangement system operating under maximal voltage equal to 110 kV was applied for experimental tests. The optical radiation was registered using a spectrophotometer. During research works, also the influence of corona generation voltage and distance between power lines was investigated. Based on the achieved results, it was stated that the highest corona intensity was found for aluminium-based lines, for both pure aluminium and aluminium with added magnesium and silicon. The lowest corona intensity was observed for chromium- and nickel-alloyed (stainless) steel.